(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives:To describe the clinical and paraclinical characteristics of peripheral arterial disease (PAD) in patients with type 2 diabetes mellitus at Viet Tiep Friendship Hospital during 2023–2024, and to assess several factors associated with PAD in the study population (by comparing patients with and without PAD). Subjects and Methods:This was a descriptive cross-sectional study with a control group, including 42 patients with type 2 diabetes mellitus and PAD, and 46 patients with type 2 diabetes mellitus without PAD. All patients were treated at the Departments of Cardiology and Nephrology–Endocrinology, Viet Tiep Friendship Hospital, from January 2023 to June 2024. Results:The mean age was 70.6 ± 9.5 years, with the ≥70-year age group accounting for the highest proportion (52.4%). Most patients with PAD (ankle–brachial index [ABI] < 0.9) had mild disease (47.6%). Among them, 57.2% were asymptomatic, while 28.6% had typical intermittent claudication. Factors such as older age, hypertension, smoking, poor glycemic control, chronic kidney disease, and atherosclerotic cardiovascular disease were associated with an increased risk of PAD in patients with type 2 diabetes mellitus.